Parental History of Dementia Is Associated with Increased Small Vessel Cerebrovascular Disease. (15th December 2019) - Stamm, Bessie C; Lao, Patrick J; Rizvi, Batool; Colon, Juliet; Igwe, Kay; Chesebro, Anthony G; Maas, Benjamin; Schupf, Nicole; Mayeux, Richard; Manly, Jennifer J; Brickman, Adam M
Abstract: Background: Small vessel cerebrovascular dysfunction that manifests on magnetic resonance imaging (MRI) as white matter hyperintensities (WMH) is linked to increased risk and progression of Alzheimer's disease (AD), but there is considerable debate about whether it represents a core feature of the disease. Parental history of dementia is a risk factor for AD, suggesting a strong heritable component; the examination of the extent to which parental history of dementia is associated with cerebrovascular disease could provide insight into the aggregation of AD and cerebrovascular disease. Methods: This study included 481 community-dwelling older adults (mean age = 74.07 ± 5.81; 56% women) with available MRI scans. Participants were classified as having a parental history of dementia or having no parental history based on self-report. Total WMH values were calculated and compared between the two groups with general linear models, adjusting for relevant covariates. We also compared WMH volume between those with a reported sibling history of dementia and those without. Results: One hundred twelve participants reported having a parental history of dementia and 369 reported no parental history. Those with parental history had greater total WMH volume than those without ( F = 4.17, p = .042, partial η  2 = 0.009). Results were strongest for those with maternal versus paternal history ( F = 2.43, p = .089, partial η  2 = 0.010 vs <0.001) and among Hispanic ( F = 5.57, p = .020, partial η  2 = 0.038) and non-Hispanic White participants ( F = 4.17, p = .042, partial η  2 = 0.009). Those with reported sibling history of dementia did not differ from those without. Conclusions: Older adults with parental, particularly maternal, history of dementia have increased WMH. The results highlight the possibility that cerebrovascular changes are a core feature of AD, as WMH severity and parental history aggregate together.